PROFIL TITER ANTIBODI Newcastle Disease (ND) dan Avian Influenza (AI) PADA ITIK PETELUR FASE STARTER DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Mega Filly Numay; Purnama Edy Santosa; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aimed to determine the antibody titre against Newcastle Disease (ND) and Avian Influenza(AI) in laying duck of starter phase in Gadingrejo Subdistrict Pringsewu District, Lampung Province.This study has been conducted in December--January 2014. The method used in this study weresurvey method and sample collecting by method of purposive sampling. The data analysis used in thisstudy was descriptive analysis. Based on the result of Hemaglutination Inhibition (HI) test on AvianInfluenza in laying duck of starter phase in Gadingrejo Subdistrict, there were 38% ducks that showedseropositive result on AI with the score of 21 and the highest score of 25 from Wonodadi Village.There were 62% ducks showed seronegative result on AI (20). Based on the result of HI test ofNewcastle Disease in laying duck of starter phase in Gadingrejo Subdistrict Pringsewu District, therewere 5% ducks that showed seropositive result with the titre score of 23 and 95% ducks withseronegative result on ND (20). The level of uniformity on AI totally was granted the score of 38%and the level of uniformity on ND totally was 5%.